The sustainability curriculum : the challenge for higher education - Blewitt, John, 1957-; Cullingford, Cedric (Routledge, 2013)
The links between education and sustainable development are deepening, although subject to much controversy and debate. The success of the sustainability discourse depends both on the pedagogic and research functions of higher education. Similarly, for higher education itself to remain relevant and engaged it faces pressure not only to integrate the insights and lessons drawn from the perspective of sustainable development, but also to be responsive to scrutiny of its own practices in relation to sustainability. Among professionals in higher education, sustainable development has its supporters and detractors. It is embraced by some individuals and departments while being perceived by others as a threat to the coherence of particular disciplines. Although it is not currently an academic discipline in its own right, increasing public and professional familiarity with the term, and the increasing urgency of global calls for the implementation of sustainable development mean that this is rapidly changing. This volume analyses the impact of the concepts and practices of sustainability and sustainable development on various academic disciplines, institutional practices, fields of study and methods of enquiry. The contributors, drawn from a wide-range of disciplines, perspectives, educational levels and institutional contexts, examine the purpose of the modern university and the nature of sustainable education, which includes exploring links to social movements for sustainability projects, curriculum change, culture and biodiversity, values relating to gender equality and global responsibility, and case studies on the transformation, or otherwise, of some specific disciplines.